Combined effects of fuel injection pressure and injector nozzle holes on the performance of preheated palm oil methyl ester used in a diesel engine. Issue 1 (2nd January 2020) - Walle Mekonen, Menelik; Sahoo, Niranjan
Abstract: This paper presents the impact of preheated palm oil methyl ester) (POME) properties and examines the consequences of varying fuel injection pressure (IP), fuel injection timing (IT) and injector nozzle hole number (IJNHN) for improving the combustion quality in a diesel engine, by evaluating the performance parameters, combustion characteristics and emissions. The fuel IPs changed from 188 to 224 bar (with an increment of 12 bar) at fuel ITs 19°, 23° and 27° Before Top Dead Center (BTDC) with a variation of IJNHN (3–5) each 0.3 mm in diameter. The test results revealed that the kinematic viscosity and density of POME decreased slowly with an increase in fuel temperature. At 114 °C, the viscosity and density of POME decreased to close to that of diesel fuel. Preheating POME improved engine brake specific fuel consumption (BSFC), brake thermal efficiency (BTHE) and emissions of CO and Hydro Carbon (HC), with a slight increase of NOx . The results indicate that increased fuel IP of 212 bar and an advanced IT of 27° BTDC with a four-hole IJNHN for preheated POME (114 °C) was the best combination for overall improvement in BSFC and BTHE with reduced emissions (of CO and HC) with respect to baseline diesel.